Intracellular neutralization of virus by immunoglobulin A antibodies. - Mazanec, M B (1992)
IgA is thought to neutralize viruses at the epithelial surface of mucous membranes by preventing their attachment. Since IgA, a polymeric immunoglobulin, is transported through the lining of epithelial cells by the polymeric-immunoglobulin receptor and since viruses are obligate intracellular parasites, we hypothesized that IgA antibodies may also interfere with viral replication by binding to newly synthesized viral proteins within infected cells. Polarized monolayers of Madin-Darby canine kidney epithelial cells expressing the polymeric-immunoglobulin receptor were infected on the apical surface with Sendai virus. Anti-Sendai virus IgA monoclonal antibody delivered from the basolateral surface colocalized with viral protein within the cell, as documented by immunofluorescence. More importantly, anti-viral IgA reduced virus titers greater than 1000-fold (P less than 0.0001) in apical supernatants and greater than 10-fold (P less than 0.0001) in cell lysates from monolayers treated with anti-viral IgA compared with those treated with either anti-viral IgG or an irrelevant IgA monoclonal antibody. We believe that the differences in viral titers between cell layers treated with specific IgA, which enters the epithelial cell by binding to the polymeric-immunoglobulin receptor, and those treated with specific IgG, which does not enter the cells, or irrelevant IgA indicate that specific intracellular IgA antibodies can inhibit viral replication. Thus, in addition to the classical role of humoral antibodies in extracellular defense, IgA antibody may be able to neutralize microbial pathogens intracellularly, giving IgA a role in host defense that has traditionally been reserved for cell-mediated immunity.